The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/0370-44672022750035
|View full text |Cite
|
Sign up to set email alerts
|

The BigFLUX Magnetic Matrix Technology

Abstract: The Magnetic separation of ultra-fine ore particles has always posed a challenge to the JONES/WHIMS process. Despite many advances in this technology, no effective improvement has been made to its core component: The Magnetic Matrix. The current approach to separate ultra-fine particles teaches that the gap of the matrix and its teeth size must be smaller than usual in order to accommodate the small size of the particles. However, practice proved this approach to be far from ideal. The closing of the gap betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%
“…Several authors have demonstrated a series of new technologies that could enhance magnetic separation processes through the development of new characterization techniques [27], equipment's [28][29][30][31][32][33][34] and the use of different matrices in high-intensity magnetic separation [35][36][37][38][39]. Such alternatives may result in significant gains in capacity, fines recovery, quality, and metallurgical recovery, as they make use of existing capacity and require low capital investment.…”
Section: Otimização Da Separação Magnética Da Hematita Contida No Pro...mentioning
confidence: 99%
“…Ademais, alguns fornecedores de equipamentos já consolidados como os concentradores WHIMS (Wet High Intensity Magnetic Separator) , têm desenvolvido matrizes (Ribeiro, Ribeiro e Vieira, 2022) que melhoram a performance desses dispositivos quando utilizados para concentração de minérios finos.…”
Section: Introductionunclassified